Peran Pengambilgunaan Teknik Perbaikan Terus-Menerus (Continuous improvement Techniques) dalam Meningkatkan Kinerja Operasional Perusahaan - Lena Ellitan (Jurnal Manajemen Maranatha, 2002)
Manufacturing excellence often results from the combined successive incremental improvement techniques and capital investment in technology. This research focuses successive incremental improvement techniques that considered as success factor of firms‘ competitive advantage. Succesive incremental improvement techniques could streamline the production process through the elimination of non-value added activities. Operational performance was evaluated in term of productivity, cost effectiveness, quality, flexibility and delivery. The hypotheses predict that adoption successive incremental improvement techniques e.g. Total Quality Management (TQM). Just In Time (JlT), Total Productive Manufacturing (TPM), and Manufacturing Resources Planning (MRP2) determine the operational performance of the organizations.The relationship between successive incremental techniques and operational performance is examined. as well. The information was collected through mailed questionnaires. Respondents were CEOs of large manufacturing firms in Indonesia. The questionnaires were sent to 500 CEOs of large manufacturing firms, a total of 104 responses were collected (a 21.05% response rate). The hypotheses were testedusing regression analysis. The results indicate: l. TQM is needed to enhance product and process quality. (2). JIT has an important role to improve productivity, cost efficience, flexibility, and delivery reliability. (3). TPM does not have a significant impact on the all dimensions of operational performance. (4) MRP2 is a practise that important to increase productivity, flexibility and delivery performance. It can be concluded that the hypotheses are partially accepted.Kata Kunci: Total Quality Management (TQM) Just In Time (JlT), Total Productive Manufacturing (TPM), and Manufacturing Resources Planning (MRP2)